Nanoemulsions in food technology : development, characterization, and applications - Ahmad, Javed (Chemist); Nollet, Leo M. L., 1948- (CRC Press, 2021)
"Divided into three sections, Nanoemulsions in Food Technology: Development, Characterization, and Applications will provide in-depth information and comprehensive discussion over technologies, physical and nanostructural characterization, as well as applicability of the nanoemulsion technique in food sciences. It describes the techniques involved in nanoemulsion characterization, mainly dealing with interfacial and nanostructural characterization of nanoemulsions, different physical characterization techniques, as well as various imaging and separation techniques involved in its characterization"- Resumé vydavatel
Keywords: nanochemie; potravinářství; biotechnologie; emulze; nanochemistry; food industry and trade; biotechnology; emulsions; elektronické knihy; sborníky; electronic books; papers of several authors